The drosophilid fauna (Diptera, Drosophilidae) of the transition between the Pampa and Atlantic Forest Biomes in the state of Rio Grande do Sul, southern Brazil: first records - Hochmüller, Cleverton J.C.; Lopes-da-Silva, Marcelo; Valente, Vera L.S.; Schmitz, Hermes J. (Papéis Avulsos de Zoologia, 2010)
Although studies on drosophilid (Diptera, Drosophilidae) assemblages have become relatively abundant in the past decades, many environments remain to be searched. The present study investigates the composition, the species abundances and the richness of the drosophilid assemblages in two localities of the municipality of Cruz Alta, northwestern region of the state of Rio Grande do Sul, a point of contact between the biomes Atlantic Forest and Pampa: (i) an urban area (2007), constituted by a domestic orchard with Citrus trees, and (ii) a forested area, in Centro de Educação, Pesquisa e Proteção Ambiental - CEPPA (2008/2009), of Universidade de Cruz Alta, located in a fragment of riparian forest. Collections were conducted using fermented banana-baited traps and repeated periodically. A total of 7,428 individuals were caught, belonging to two subfamilies, six genera and 53 species. In the urban area, 22 species were found, from two genera (N = 2,421), while in the forested area 46 species were found, from six genera (N = 5,007). Six exotic species were found, markedly more abundant in the urban area, where they corresponded to 95% of the specimens, in comparison to 50% in the forest. Between the Neotropical species, the most common were Drosophila maculifrons Duda and D. polymorpha Dobzhansky & Pavan. Only D. simulans Sturtevant was captured in all samples in both localities. The present survey represents the first records for the state of Rio Grande do Sul of the D. canalinea and D. virilis species groups and the species D. arassari Cunha & Frota-Pessoa, D. fuscolineata Duda, D. nigricruria Patterson & Mainland, D. papei Bächli & Vilela, D. senei Vilela, D. trifilum Frota-Pessoa, D. virilis Sturtevant, Leucophenga maculosa (Coquillett) and Rhinoleucophenga obesa (Loew). Furthermore, it also represents the first record for the state of the genera Amiota Loew, Leucophenga Mik and Rhinoleucophenga Hendel and of the subfamily Steganinae. So, the present survey raises the number of drosophilid species recorded for the state from 66 to 75, the number of genera from five to eight, and subfamilies from one to two.